Buletin Peternakan : Pengaruh Suplementasi Probiotik Bakteri Asam Laktat Terhadap Histomorfologi Usus Dan Performan Puyuh Jantan - Sapta Chandra Marnadi Hidayat, Sri Harimurti, Lies Mira yusiati (Peternakan UGM, 2016)
The present study was conducted to investigate the effects of lactic acid bacteria (LAB) probiotics supplementation on intestinal histomorpholgy and performance of male quail.